Optimal phasor measurement units placement for fault location on overhead electric power distribution feeders - Bíscaro, A. A P [UNESP]; Pereira, R. A F [UNESP]; Mantovani, J. R S [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper proposes a new approach for optimal phasor measurement units placement for fault location on electric power distribution systems using Greedy Randomized Adaptive Search Procedure metaheuristic and Monte Carlo simulation. The optimized placement model herein proposed is a general methodology that can be used to place devices aiming to record the voltage sag magnitudes for any fault location algorithm that uses voltage information measured at a limited set of nodes along the feeder. An overhead, three-phase, three-wire, 13.8 kV, 134-node, real-life feeder model is used to evaluate the algorithm. Tests show that the results of the fault location methodology were improved thanks to the new optimized allocation of the meters pinpointed using this methodology. © 2011 IEEE.
Keywords: fault location; Monte Carlo methods and optimization methods; Optimal allocation; phasor measurement units (PMUs); Electric power; Electric power distribution systems; Fault location; Fault location algorithms; General methodologies; Greedy randomized adaptive search procedure; Metaheuristic; Monte Carlo Simulation; Optimized allocation; Phasor measurement unit; Placement model; Voltage sags; Algorithms; Computer simulation; Electric load distribution; Electric power distribution; Electric power system interconnection; Electric power transmission; Feeding; Optimization; Phase measurement; Thermoelectric equipment; Units of measurement; Monte Carlo methods